Interrogation of gender dynamics in pornoraphic films: a case study of Tarzan X shame of Jane, Kelly’s Public disgrace and 50 Shades of grey XXX adaption - Pasipanodya, Isabel (Midlands State University, 2017)
The Research Thesis has the aim of interrogating gender dynamics in pornographic films. The research focuses on masculine characteristics, feminine characteristics, masculine and feminine relationships and film techniques used and their effect. The study will interrogate these gender dynamics in three films which are Kelly’s Public Disgrace by kink, Tarzan X Shame of Jane and Fifty Shades of Grey XXX Adaption. Qualitative research methodology was used to carry out the research. Liberal feminism which advocates for women’s equality, freedom, dignity and the full enforcement of existing anti discriminatory laws on behalf of women was used. The Researcher found that pornography is a genre that does depict masculine and feminine characteristics. It also leaves some women traumatized and some eventually contact STIs and GPV. Masculine characteristics include being tough skinned, hard, strong, aggressive, dominant, independent and intelligent. Feminine characteristics include being soft, emotional, subordinate and submissive. It is a genre just like any genre where the degradation of women is normalized. It is normalized due to patriarchal societies where gender relations are in favour of males, which is why women willingly accept to be degraded. In order for masculine characteristics to be brought out clearly there should be feminine characteristics as they complement each other. Pornography makers make use of film techniques that help in making it more realistic like the use of make-up, appropriate camera angles and positions and the right stereotypic body size. All three films portrayed masculine, feminine and the masculine-feminine relationship although they had differences like setting and storylines. The researcher recommends porn movies to emphasize on human equality, dignity, safety and mutual fulfillment.